Early-life nutritional supplementation protects against home environmental risks in Ghanaian children's social-emotional development - Partington, Lindsey C.; Yuan, Haiying; Demuyakor, Maku E.; Adu-Afarwuah, Seth; Guyer, Amanda E.; Dewey, Kathryn G.; Kumordzie, Sika M.; Oaks, Brietta M.; Arnold, Charles D.; Prado, Elizabeth L.; Hastings, Paul D. (Frontiers in Nutrition, 2025)
IntroductionThis study examines how an early-life small-quantity lipid-based nutrient supplement (LNS) interacts with the home environment to influence Ghanaian children's social-emotional functioning at preschool age.MethodIn a randomized controlled trial, 1,320 Ghanaian women received either daily LNS, multiple micronutrients (MMN) or iron and folic acid (IFA) during pregnancy through 6 months postpartum. Infants in the LNS group received the daily supplement from 6 to 18 months. The IFA and MMN groups were combined to be the control group. At 4–6 years (n = 966), we assessed children's home environments (caregiver responsivity, negative behavior acceptance, physical environment, learning materials, academic stimulation) and their social-emotional strengths and difficulties.ResultsBoth LNS and higher quality home environments—particularly caregiver responsivity and negative behavior acceptance—predicted children having fewer social-emotional difficulties. LNS supplementation moderated relations between the home environment and children's hyperactivity/inattention and total difficulties. Living in a safer physical environment was related to fewer hyperactivity/inattention problems and total difficulties only for children who received LNS. Less academic stimulation was related to more hyperactivity/inattention only for children in the control group.ConclusionEarly-life LNS supplementation and supportive home environments reduce social-emotional difficulties in Ghanaian children. Nutritional interventions are most effective in the context of safe, stimulating households, demonstrating that integrated interventions support children's wellbeing in low- and middle-income countries.Clinical trial registrationclinicaltrials.gov; identifier: NCT00970866.